Exploration of Anti-FABP3 Aptamer Conformation Using Coarse-Grained Molecular Dynamics Simulation - Aathirah, A Sayyidatina; Hardianto, Ari; Gaffar, Shabarni (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Aptamers have been extensively utilized in the development of diagnostic and therapeutic methodologies for a variety of diseases. Aptamer N13, obtained through the SELEX process in previous research, has been identified as an anti-FABP3 ssDNA aptamer to enhance diagnostic techniques for myocardial infarction. This study provides an in-depth examination of the conformation and structural dynamics of aptamer N13 using in-silico methods. These include secondary structure prediction via DNA-fold, 3D structures modeling through RNA-Composer, and coarse-grained molecular dynamics (MD) simulations with SIRAH AMBER. The 83 μs MD simulation results reveal that the predicted conformation generally struggles to maintain stability, as indicated by the RMSD values and their fluctuations. However, residues 1-50 demonstrate relatively stable conformations, particularly beyond the 40 μs point in the simulation. In contrast, residues 51-90, constituting the free end, exhibit persistent conformational instability. This instability is likely attributable to their single-stranded and free nature compared to the other regions characterized by loops that confer greater stability. Our findings suggest that the predicted conformation from existing tools does not yet provide the most stable reference structure, necessitating further exploration through extended molecular dynamics simulations. While current simulations offer a relatively stable conformational reference, additional simulations are warranted to determine the most stable configuration of the free-end region, thereby elucidating its role in the aptamer’s affinity and specificity